(untitled) (Vietnam Journal of Community Medicine, 2022)
Rationale: Metabolic syndrome (MetS) has been a public health issue in the spotlight recently. The metabolic syndrome is increasing in the big cities and the red river delta provinces such as Thai Binh, where there is an incremental prevalence of MetS. Therefore, it is necessary to identify the prevalence of metabolic syndrome in people aged 25 to 64 in Thai Binh. Research objective: Identifying some factors relating to metabolic syndrome in people aged 25 to 64 in Thai Binh province. Research objects and methodology: The cross - sectional study was conducted on 1336 people aged 25-64 years, aiming to identify the prevalence of Metabolic Syndrome (MetS) in adult people in 6 districts in Thai Binh province in 2019. Results: Male and female participants accounted for 49.9% and 50.1%, respectively. The mean waist was 77.19 ± 8.12cm; the mean systolic blood pressure was 121.10 ± 18.14 mmHg, the mean blood glucose was 5.33 ± 1.07 mmol/l, the mean triglyceride was 1.89 ± 1.11 mmol, the mean HDL-C was 1.19 ± 0.39 mmol/l. The prevalence of MetS was 28.4%. The proportion of engagement with 3 components of MetS accounted for 29.7% in wome and 27.1% in men. The proportion of engagement with 2 pieces of MetS was 30% in men and 22.1% in women. Conclusion: The prevalence of Metabolic Syndrome was 28.4%